2022
DOI: 10.3389/fsurg.2022.986297
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery in liver cirrhosis

Abstract: IntroductionObesity is frequently associated with its hepatic manifestation, the nonalcoholic fatty liver disease (NAFLD). The most effective treatment for morbid obesity is bariatric surgery (BS) also improving NAFLD and liver function. In patients where NAFLD has already progressed to liver cirrhosis, BS can be considered a high-risk procedure. Hence, consideration of the procedure and the most appropriate timing is crucial.Material and MethodsObese patients suffering from NAFLD who underwent BS from two Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In most patients in this series, cirrhosis was however incidentally diagnosed during protocol biopsy during MBS. In a small number, MBS was performed during preparation for LT. A few patients with TIPS were included 59 . Based on the overall literature, MBS in patients with compensated cirrhosis seems to be safe, however a careful patient selection is key and optimizing patients' secondary comorbidities needs to be done before surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most patients in this series, cirrhosis was however incidentally diagnosed during protocol biopsy during MBS. In a small number, MBS was performed during preparation for LT. A few patients with TIPS were included 59 . Based on the overall literature, MBS in patients with compensated cirrhosis seems to be safe, however a careful patient selection is key and optimizing patients' secondary comorbidities needs to be done before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with decompensated cirrhosis had much higher mortality rates compared to those with more stable liver disease ( 59 Based on the overall literature, MBS in patients with compensated cirrhosis seems to be safe, however a careful patient selection is key and optimizing patients' secondary comorbidities needs to be done before surgery.…”
Section: Transplant Surgeonsmentioning
confidence: 99%
“…BS has been shown to induce NASH disappearance in nearly 85% (95%CI: 75.8%-92.2%) of patients and to decrease fibrosis in 33.8% of patients (95%CI: 23.6%-45.2%) with NASH at 1 year after surgery[ 135 ]. Another clinical study showed that excessive weight loss shown in patients with cirrhosis with 73% (33%–167%), 85% (33%–190%), and 73% (29%–107%) after 1, 2, and 3 years of BS[ 136 ], respectively. Among 27 patients with cirrhosis, 3 patients had significant improvement in liver function and did not need liver transplantation, whereas 2 out of 27 patients had deleterious liver function post-BS treatment[ 136 ].…”
Section: Current Treatment Options For Liver Fibrosismentioning
confidence: 99%
“…Another clinical study showed that excessive weight loss shown in patients with cirrhosis with 73% (33%–167%), 85% (33%–190%), and 73% (29%–107%) after 1, 2, and 3 years of BS[ 136 ], respectively. Among 27 patients with cirrhosis, 3 patients had significant improvement in liver function and did not need liver transplantation, whereas 2 out of 27 patients had deleterious liver function post-BS treatment[ 136 ].…”
Section: Current Treatment Options For Liver Fibrosismentioning
confidence: 99%